Edukasi makanan bergizi dan seimbang untuk cegah anemia dalam kehamilan di Kelurahan Sungai Bangkong, Pontianak, Kalimantan Barat - Marsela Renasari Presty; Agnes Dwiana Widi Astuti; Siti Fadlilah; Intanwati Intanwati (Nur Science Institute, 2026)
Pregnancy is a physiological process that leads to various changes in a woman’s body, including physical, psychological, and social adjustments. During this period, the body requires increased nutritional intake to support maternal health and fetal development. One of the essential nutrients is iron, which plays a crucial role in the formation of red blood cells, ensures adequate oxygen transport, supports fetal growth, and prepares the mother for potential blood loss during childbirth. Pregnant women are at risk of developing anemia if their iron requirements are not adequately met. Anemia is a condition that can negatively affect maternal health and increase the risk of complications such as preterm birth and low birth weight. This activity aimed to provide education on the importance of a balanced, nutritious diet to prevent anemia during pregnancy. Data collection revealed that 38 pregnant women with anemia resided in Sungai Bangkong Village, of whom 11 participated in the educational session held at Alianyang Public Health Center on January 28, 2026. The program included pretest and posttest assessments, delivery of material through lectures and discussions, and demonstrations of nutritious meal preparation. The T-test results indicated a significant increase in knowledge.